Subinguinal orchiectomy—A minimally invasive approach to open surgery. Issue 5 (13th August 2020) - Anderson, Elliot; Pascoe, Claire; Sathianathen, Niranjan; Katz, Darren; Murphy, Declan; Lawrentschuk, Nathan
Abstract: Objectives: To determine the rate of morbidity and assess the oncological outcomes for the subinguinal orchidectomy technique. Background: Radical inguinal orchiectomy is the definitive management for a testicular mass suspicious for malignancy. The standard approach involves the division of the spermatic cord at the internal inguinal ring. In addition to the morbidity of a significant incision through skin and fascia, a known complication is damage to the nerves within the canal leading to local hypoesthesia or persistent inguinal and scrotal neuralgia. The subinguinal orchiectomy technique avoids opening the inguinal canal by excising the spermatic cord at the external inguinal ring. Methods: Patient data from three urologists who routinely perform subinguinal orchiectomies for suspected testicular malignancy was collected. A retrospective analysis between March 2011 and March 2019 was undertaken evaluating demographic, clinical, and histological data points. Descriptive analysis of oncological and surgical outcomes of subinguinal orchiectomy for testicular mass was performed. Descriptive analysis of oncological and surgical outcomes of subinguinal orchiectomy for testicular mass was performed. Results: About 42 orchiectomies performed via the subinguinal approach were identified. The median age was 38 years (range 22‐72) and mean follow‐up time was 18.4 months (range 0.59‐61). Of the 38 patients with testicular cancer, histopathology showed 26 with pT1, 9 with pT2, and 3 with pT3 disease. Three patients had involvement of the cord, with one patient having a positive surgical margin secondary to venous invasion. No patients experienced neuropathic complications, hernia, or wound break down. Conclusion: These data suggest that subinguinal orchiectomy provides acceptable oncological outcomes, comparable to a traditional technique, and may decrease the risk of neuropathic injury and incisional/inguinal hernia. Further investigation with a larger, prospective series is required.